Investigation of the effect of some salts on the rheological properties of xanthan gum and gum arabic present in a drilling fluid (2022)
The rheological properties of a drilling fluid are important because they allow for extensive examination of the viscosity, fluid flow profile, pressure loss, equivalent circulation density, and hole cleaning capability making it the foundation for all wellbore hydraulics. The viscosity, gel strength, and yield point of Gum Arabic and Xanthan Gum contained in a fresh water-based drilling fluid were investigated in the presence of three distinct salts: calcium chloride (CaCl2), potassium chloride (KCl), and sodium chloride (NaCl). The salts were introduced separately to three distinct fresh water-based drilling fluid samples in increasing weights. The Fann V-G viscometer was used for the required rheology properties measuring the RPM and gel strength. The plastic viscosity, apparent viscosity, and yield point were calculated from the experimental data. With increasing the salt concentration, the plastic viscosity, apparent viscosity, yield point, and gel strength all decreased, which was observed for all three salts used. This research aimed to investigate the effect of three different salts; Calcium chloride (CaCl2), Potassium Chloride (KCl), and Sodium Chloride (NaCl) on the rheological properties of Gum Arabic and Xanthan Gum viscosified water-based drilling fluid.